Aspects of the Physical Environment in the Ecosystems Services Scenarios - Alarsa, Cecilia; Furlan, Sueli Angelo; Colângelo, Antonio Carlos (Revista do Departamento de Geografia, 2018)
The way of life established on the planet depends on the natural resources and the benefits they offer. Human transformations in natural systems intensified in the twentieth century and numerous protection strategies were developed and proposed in the scientific and institutional field. Ecosystem services emerged in this movement aiming at identifying the capacity to support natural capital stocks in relation to the needs and benefits associated with the human being and their respective capacity to recover and regenerate the system, which is considered as a cascade of interconnected processes. Considering that ecosystems are the interaction between biotic and abiotic factors, and that ecosystem functions integrate aspects of the physical, biotic and socioeconomic environments, the objective of this research was to identify how aspects of the physical environment are addressed in the thematic of ecosystem services. Through systematic bibliographic review it was observed that there are distinct trends in the business, institutional and academic sectors. In addition, two weaknesses accompany knowledge about ecosystem services: (i) the differentiation of concepts and methodologies, where the applications vary according to the objective and (ii) the gaps between the interactions of the ecosystem functions, where the aspects of the physical environment are considered if they are identified as priorities for the research. It is considered that this gap in the physical environment can be filled with studies of susceptibility to the processes of surface dynamics, in landscape units grouped by similarity of variables, being a functional basis for the proper evaluation of ecosystem services, highlighting the insertion of this theme in the area knowledge of physical geography.